Effects of Low Intensity Exercise Against Apoptosis and Oxidative Stress in Streptozotocin-induced Diabetic Rat Heart - Kanter, M.; Aksu, F.; Takir, M.; Kostek, O.; Kanter, B.; Oymagil, A. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background The aim of this study was to investigate the effects of low intensity exercise on heart of streptozotocin (STZ)-induced diabetic rats.Materials and Methods The rats were randomly divided into 3 experimental groups: A (control), B (diabetic untreated), and C (diabetic treated with low intensity exercise); each group contains 8 animals. B and C groups received STZ. Diabetes was induced in 2 groups by a single intraperitoneal (i.p) injection of STZ (40 mg/kg, freshly dissolved in 0,1 M citrate buffer, pH 4.2). 2 days after STZ treatment, diabetes in 2 experimental groups was confirmed by measuring blood glucose levels. Rats with blood glucose levels of 250 mg/dl or higher were considered to be diabetic. Animals in the exercise group were made to run the treadmill once a day for 4 consecutive weeks. Exercise started 3 days prior to STZ administration.Results After induction of diabetes, histological abnormalities were observed, including myofibrillar loss, vacuolization of cytoplasm and irregularity of myofibrils. These alterations were attenuated by low intensity exercise. Our data indicates a significant reduction of oxidative stress and apoptosis in cardiomyocytes after exercise. Treatment of diabetic animals with low intensity exercise, decreased the elevated tissue malondialdehyde (MDA) levels and increased the reduced activities of the enzymatic antioxidants superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) in cardiac tissue.Conclusion These findings suggest that low intensity exercise has a therapeutic protective effect in diabetes by decreasing oxidative stress and apoptosis, and by preservation of myocardial integrity.
Keywords: diabetes; low intensity exercise; oxidative stress; apoptosis; heart tissue